SISTEM PAKAR PENYAKIT ALERGI KULIT PADA MANUSIA BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract - The development in science and technology especially in the field of mobile devices based on android operating system is currently undergoing rapid development and the general public interest. Skin allergy is a group of skin diseases that is based on the allergic mechanism (antigenantibody).These diseases, just like other allergic diseases, arise due to excessive sensitization reactions. The aim of this paper is the creation of applications for the android-based expert system that allows users to diagnose skin allergy through symptoms suffered. Therefore, users will easy to get possibility information of the diseases. This system uses a technique method (forward chaining). This system is expected to facilitatethe process of diagnosing the disease, because the androidmobile based expert system can be used anywhere and anytime.Keywords - Android, Skin Allergies, Expert System, ForwardChaining.